The Strategic Leadership In The Procurement Of Modern Naval Defense Equipment: Responding To Indonesia’s Maritime Geopolitical Challenges - David Candra Viasco; Willy Arafah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The evolving maritime geopolitical dynamics of the Indo-Pacific—marked by great-power rivalry, grey-zone activities in the South China Sea, and increasingly complex maritime threats—place Indonesia in a strategic environment that demands sustained naval modernization. As the world’s largest archipelagic state, the security of sea lines of communication, protection of maritime sovereignty, and safeguarding of marine resources render the procurement of Indonesian Navy (TNI AL) defense equipment a strategic function rather than a mere logistical activity. This study aims to analyze the role of strategic leadership in shaping the procurement direction of modern naval defense equipment and to explain the linkage between geopolitical dynamics, strategic leadership, defense management, and procurement outcomes. The research employs a qualitative approach through a Systematic Literature Review (SLR) of scholarship on strategic leadership, defense acquisition management, and maritime security. The findings indicate that strategic leadership serves as the critical bridge between geopolitical threat perceptions and capability decisions, while strategic management functions as the institutional mechanism translating vision into capability planning and acquisition programs. Modern naval procurement ultimately operates as an instrument of maritime deterrence by enhancing credibility, interoperability, and operational readiness. The study concludes that TNI AL modernization constitutes a leadership-driven strategic transformation rather than simply a process of military expenditure.